STUDY OF REACTIVE POWER COMPENSATION USING STATIC VAR COMPENSTOR (International Journal of Engineering and Computer Science, 2014)
This paper presents an application of a Static Var Compensator (SVC). A SVC is based on Power Electronics and other static devices known as FACTS (Flexible AC Transmission Systems) Controllers which it could be used to increase the capacity and the flexibility of a broadcast network. The effect of wind generators on power quality is an important issue; non uniform power invention causes differences in system voltage and frequency. Therefore wind farm requires high reactive power compensation; the advances in high power semiconducting devices have led to the development of FACTS. The FACTS device such as SVC inject reactive power into the system which helps in maintaining a better voltage profile.